PROFITABILITY UNDER COST INTENSITY: HOUSEHOLD LIVELIHOODS IN CATFISH FARMING IN PALEMBANG - Anilda Satya Ningrum; Desi Aryani; Mohamad Amin (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2026)
Catfish (Clarias gariepinus) farming is the dominant freshwater aquaculture in Palembang, South Sumatra, serving as both a key livelihood and a major source of local food security. Despite its importance, few studies have examined its economic contribution at the household level. This study analysed the income structure of 60 catfish-farming households in Sukarami, Sematang Borang, Gandus, and Plaju districts, focusing on costs, profitability, and diversification. Data were collected during January–June 2025 through structured interviews, field observations, and official records. Findings show that production is highly operationally intensive, with feed and seed accounting for 94.30 % of total costs. Despite this, catfish farming remains profitable, generating an average net income of IDR 14.14 million per cycle, or IDR 56.54 million annually. The activity accounted for 61.30% of household income, confirming its role as the primary livelihood source. Complementary activities, including Pangasius sp. farming (15.50 %) and non-fisheries income (23.20 %), provided diversification that mitigates risks and stabilizes cash flow. Overall, catfish aquaculture sustains household economies in Palembang but remains highly vulnerable to fluctuations in input prices and market instability. However, the sector remains highly susceptible to fluctuations in input prices and market instability. Policy interventions should, therefore, prioritize improvements in feed efficiency, access to quality seed, and cooperative procurement, along with income diversification, to strengthen household resilience and ensure the socio-economic sustainability of small-scale aquaculture.